Hemodialysis as a rite of transition - Esperanza Vélez Vélez (Fundación para el Desarrollo de la Enfermería, 2006)
This article intends to explore the conceptual and practical application of the rites of transition model in the care of renal patients on hemodialysis treatment in our cultural environment. An ethnographic approach and narrative qualitative methodology were used, with an interpretation grounded in the constructivist paradigm. By convenient sampling, twelve patients on hemodialysis treatment were selected The immersion in hemodialysis culture and the observation process were done in the hemodialysis unit and also at patients' home , where the in-depth interviews were carried out. The analysis of patients' narratives shows the three stages of the rites of transition: separation, transition and reincorporation. The metaphoric usefulness of this model's application and its possible influence on the quality of care offered to these patients is argued.